OPINI MASYARAKAT KOTA MEDAN TERHADAP PEMBERITAAN BEGAL PADA PORTAL MEDANTALK - Akbar, Lilo; Raisyanura, Raisyanura; Syafrianda, Syafrianda (Jurnal Psikotes, 2024)
Public opinion regarding news on the Medantalk portal in presenting information is not the same as other online media, in this case the presentation of information presented by Medantalk media is entirely through video content which is much liked by young people. Considering the digital era, there are many incidents around the city of Medan which are in the public spotlight with the media. Robbery can be interpreted as a crime (criminal) such as robbery/robbery carried out by someone accompanied by violence using sharp weapons and using motorized vehicles, even sometimes committing crimes. murder of the victim and the targeted victims are usually motorbike riders. This research method uses a qualitative approach in conducting this research, namely research through observation, interviews, or document review and is descriptive in nature. The data analysis techniques that the author uses are observation, data reduction, data presentation, and drawing conclusions. The results of the research are that public opinion regarding robbery news on the MedanTalk portal has a big impact on everyday life. People feel threatened with losing their lives or property while driving.